Demographic Determinants of Art Therapy Engagement for Mental Health: A Singaporean Perspective - Hiang, Koh Sok; Fong, Christopher; Tripathi, Shilpi (Advances in Social Sciences Research Journal, 2025)
Art therapy has gained international recognition as an effective psychotherapeutic approach that enhances emotional resilience, fosters self-expression, and supports mental well-being. In Singapore, despite public mental health awareness has improved through government initiatives, the actual uptake of non-traditional therapies such as art therapy remains limited. This study investigates the demographic determinants influencing engagement with art therapy, focusing on age, income, and education among Singapore residents. A quantitative design was employed, utilizing a structured online survey with 110 participants aged 18–75 years. Data were analyzed using Spearman’s rho correlation to assess relationships between demographic variables and art therapy uptake. Results revealed a statistically significant but weak negative correlation between age and art therapy engagement (rₛ = –0.216, p < .05), indicating that younger adults are more receptive to art therapy than older participants. Conversely, correlations between income (rₛ = 0.067, p = .490) and education (rₛ = 0.051, p = .599) with art therapy utilization were weak and non-significant. Subgroup analysis suggested nuanced patterns: females aged 47–60 demonstrated greater engagement than males in the same age group, and paradoxically, affluent, highly educated individuals reported lower utilization rates, possibly due to stigma, skepticism, or lack of insurance coverage. These findings highlight a generational divide in openness to expressive therapies and reveal a disconnect between socioeconomic advantage and actual service uptake in Singapore. The results underscore the importance of addressing cultural stigma, enhancing public education on art therapy, and improving accessibility through subsidies and insurance coverage. Policymakers, healthcare providers, and educators can leverage these insights to design targeted interventions, ensuring broader and more equitable engagement with art therapy across Singapore’s diverse demographic landscape.